PERTUMBUHAN EKONOMI: PENDAPATAN ASLI DAERAH (PAD), DANA PERIMBANGAN, DAN BELANJA DAERAH DENGAN KONSUMSI SEBAGAI VARIABEL MODERATING PADA KABUPATEN ACEH TENGGARA - Rina, Rina Malahayati (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
This study is aimed to analize the influence of locally-generated revenue, equalization funds, and regionalshopping on Economic growth at District of southeast Aceh simultaneously and partially and analizingthe influence of consumption between locally-generated revenue (PAD), Equalization funds, and shoppingareas on economic growth at the district of south east aceh. Analysis of unit are the government offinancial statements and rate of economic growth the district of south east aceh 2014-2018 year thatgetted from Central Bureau of Statistics (BPS) District of south east aceh. The population of study are thelocal government district of south east aceh period 2014 – 2018. Processing of data uses panel dataprocessed by using SPSS. For testing the hypothesis, the study uses path analysis. The result showed that(1) locally-generated revenue effect to positively to economic growth, (2) the equalization funds effect tonegatively to economic growth, (3) the regional shopping effect to positively to economic growth, (4) theconsumption effect to positively to economic growth,(5) the locally-generated revenue, equalization funds,regional shooping and consumption simultaneously to economic growth, (6) the consumptionasmoderating variable so that can be strengthen or weaken the effect of locally-generated revenue,equalization funds, and regional shopping to economic growth. Next, the consumption effect to economicgrowth directly